Reduced‐rank space‐time adaptive processing algorithm based on multistage selections of angle‐Doppler filters - Zhaocheng Yang; Xiaoye Wang (IET Radar, Sonar & Navigation, 2022)
Abstract A new reduced‐rank (RR) space‐time adaptive processing (STAP) algorithm based on multistage selections of angle‐Doppler filters is proposed in the form of a generalised sidelobe canceller. First, two types of the RR auxiliary angle‐Doppler filters are designed based on the discrete Fourier basis functions. Then, a novel multistage method is implemented to select the angle‐Doppler filters by using the cross‐correlation observed at the current stage and the residual output observed at the previous stage. Finally, the asymptotic statistic performance of target detection is evaluated in terms of the conventional framework of STAP for the cases of both known and unknown covariance, which shows that the proposed algorithm is capable of providing the constant false alarm rate. Numerical examples are provided, and they demonstrate that the proposed algorithm is able to offer better performance than the existing sparsity‐based and the conventional reduced‐dimension algorithms under the intrinsic clutter motion and array gain and phase errors.